ANALYSIS OF MULTICULTURAL EDUCATION IN SHAPING THE CHARACTER OF PARTICIPANTS EDUCATE THROUGH CULTURAL DIVERSITY IN ELEMENTARY SCHOOLS - Ni Wayan Deliani; Ninda Putriayu; Rahmadani; Suherli Evarianti (Journal of Pedagogical Content Knowledge, 2026)
In the context of Indonesia’s rich cultural, ethnic, religious, linguistic, and social diversity, multicultural education is highly relevant to promoting social harmony, tolerance, and national unity. Elementary school education plays a strategic role in this process because this stage represents an important period of character formation, during which students develop values, attitudes, social identities, and patterns of interaction with others. This study aims to analyze the concept, importance, and implementation of multicultural education in elementary schools, particularly its contribution to character building through curriculum development and an inclusive school culture. This study employs a literature review method with a descriptive qualitative approach. Relevant literature concerning multicultural education, character education, cultural diversity, curriculum development, and school culture was analyzed to identify key concepts, implementation strategies, and educational implications. The findings indicate that multicultural education contributes to character development by integrating values such as tolerance, respect, empathy, equality, cooperation, and appreciation of cultural differences into learning and school activities. The implementation of multicultural education should not be limited to delivering knowledge about cultural diversity but should also be reflected in classroom interactions, learning materials, extracurricular activities, school traditions, and teachers’ exemplary behavior. An inclusive school culture provides students with opportunities to interact, collaborate, express their identities, and respect different perspectives. The study concludes that integrating multicultural education into curriculum development and school culture can strengthen students’ character and foster an inclusive, tolerant, respectful, and socially responsible generation. This approach is also relevant to strengthening national unity and realizing the principle of Bhinneka Tunggal Ika in Indonesian elementary education.